The educational services market and new trends in the state educational policy in contemporary Russia - I N Efimova; A V Makoveychuk (Vestnik Rossijskogo universiteta družby narodov. Seriâ Sociologiâ, 2015)
The article analyzes main trends in the development of the higher education system in the contemporary Russian society that seeks to form a new innovation-oriented person, a professional with a wide range of knowledge and skills including the lifelong learning ability. The authors consider the impact of universities ratings and images on the psychological aspects of enrollees’ motivation to choose a higher education institution; describe key mechanisms of the formation of a favorable information field to work with future potential students; identify the most effective channels and content of communication, as well as public opinion leaders determining the choice of a university to study in; forecast the development of such a communication policy both at the internal educational market and in the framework of the international promotion of Russian higher education and improving the quality of education and competitiveness of Russian universities at the international research and educational market. The authors consider their empirical study quite valuable for they analyzed the key trends in the development of the higher education for the period from 2011 to 2014, and indicated some guidelines for further research in the field. These trends and prospects were revealed on the data of the sociological survey conducted in Lobachevsky State University of Nizhniy Novgorod during the admission campaigns of 2011-2014.